2013
DOI: 10.1164/rccm.201209-1726oc
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics as a Novel Approach for Early Diagnosis of Pediatric Septic Shock and Its Mortality

Abstract: Rationale: Septic shock is a significant cause of morbidity and mortality in the pediatric population. Early recognition of septic shock and appropriate treatment increase survival rate; thus, developing new diagnostic tools may improve patients' outcomes. Objectives: To determine whether a metabolomics approach could be useful in the diagnosis and prognosis of septic shock in pediatric intensive care unit (PICUs). Methods: Serum samples were collected from 60 patients with septic shock, 40 PICU patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
177
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(192 citation statements)
references
References 48 publications
13
177
0
2
Order By: Relevance
“…In particular, in our study the presence of acetone ketone bodies in the urine of the septic group suggests a compensatory reaction to a reduced level of ATP. It is interesting to see that also in works on metabolomics in the literature, conducted both on animals and humans, there were increases in metabolites (in plasma and urine) which are part of the oxidative metabolism of fatty acids, such as the ketone bodies (hydroxybutyrate, acetoacetate), in septic subjects [8,[10][11][12]. Lin et al suggest that the increase in acetoacetate and hydroxybutyrate in septic rats may be correlated with major oxidation of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in our study the presence of acetone ketone bodies in the urine of the septic group suggests a compensatory reaction to a reduced level of ATP. It is interesting to see that also in works on metabolomics in the literature, conducted both on animals and humans, there were increases in metabolites (in plasma and urine) which are part of the oxidative metabolism of fatty acids, such as the ketone bodies (hydroxybutyrate, acetoacetate), in septic subjects [8,[10][11][12]. Lin et al suggest that the increase in acetoacetate and hydroxybutyrate in septic rats may be correlated with major oxidation of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolites, which may arise from resident or infecting microorganisms or their hosts, have yielded important information about the pathophysiology of many conditions. Metabolites identified by proton nuclear magnetic resonance ( 1 H-NMR) spectroscopy, gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectroscopy (LC-MS) have been used to establish diagnosis and prognosis of many infectious and noninfectious diseases (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Metabolomics, as with the other "omics," is made possible only because advanced analytics are now available.…”
mentioning
confidence: 99%
“…NMR, GC-MS and LC-MS analyses have shown that metabolomic fingerprints (metabolic biopatterns) can be used to differentiate between patients with various diseases and healthy subjects [31, 51-54, 68, 69, 76]. Additionally, 1 H NMR metabolomic analysis has also been shown to be capable of predicting mortality in children and adults with sepsis [15,32]. These studies show that the metabolomic identification of new biomarkers or biopatterns for critical care diseases and syndromes is achievable.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we investigated whether a metabolomics approach could be useful in the diagnosis and prognosis of septic shock in pediatric intensive care units (PICUs) [32]. We were able to successfully separate metabolic profiles of PICU septic shock patients from non-infected PICU patients (patients with systemic inflammatory response syndrome but not suspected of having an infection) and healthy children.…”
Section: Application Of Nmr-based Metabolomicsmentioning
confidence: 99%